Improving spatial thinking skills among undergraduate geology students through short online training exercises. Issue 18 (12th December 2018) - Gold, Anne U.; Pendergast, Philip M.; Ormand, Carol J.; Budd, David A.; Mueller, Karl J.
ABSTRACT: Spatial reasoning is a critical skill in the Geosciences. Using a randomized control study with 592 undergraduate students enrolled in introductory and advanced Geology courses, our data indicates that regular, short interventions throughout an academic semester improve students' spatial thinking skills significantly with a moderate to large effect size when compared to an instruction-as-usual control group. We found evidence for additional gains in students who participated also in hands-on training interventions. We found even larger training effects on students who achieved correct scores of >50% on the practice modules, with gains of almost three-quarter of a standard deviation relative to their baseline scores. Male and female students display significant differences in spatial skills, with males outperforming females. Training resulted in similar magnitudes of improvement in both genders, so we see no evidence that the interventions closed the gender gap. Using the initial performance as a baseline, poor performers' spatial skills appear to improve through practice at the same rate as their peers. We argue that 15.4% of students improve their spatial skills through participation in the training towards a threshold that appears to be critical for participation in STEM careers. On a reflection survey, half of the students reported that they felt their spatial thinking skills improved through their participation, and over a third found the training beneficial for their overall learning in Geology or other classes. We hypothesise that formal training opportunities for spatial reasoning could increase the potential pool of students who successfully enter and succeed in Geoscience careers.